2017
DOI: 10.1053/j.gastro.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Antibody-Based Strategies for Diagnosis of Pediatric Celiac Disease Without Biopsy

Abstract: In a prospective study, we validated the TTG-IgA procedure and the TTG-DGL procedure in identification of pediatric patients with or without celiac disease, without biopsy. German Clinical Trials Registry no.: DRKS00003854.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
101
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 26 publications
(31 reference statements)
11
101
1
12
Order By: Relevance
“…This finding is similar to other validation studies proposing to omit biopsy for children with tTGIgA > 10-fold the upper normal limit, when associated with other criteria [5, 24, 27, 28]. …”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to other validation studies proposing to omit biopsy for children with tTGIgA > 10-fold the upper normal limit, when associated with other criteria [5, 24, 27, 28]. …”
Section: Discussionsupporting
confidence: 90%
“…6 Unfortunately, not all studies evaluating the criteria have included EMA. 10 In line with paediatric studies, 7,8 we observed excellent agreement between EMA positivity and tTG-ab >10× ULN, giving further credibility for the results. One might ask whether laborious EMA was required in all cases, but currently it could be considered as inexpensive quality control.…”
Section: Discussionsupporting
confidence: 86%
“…Due to this and the aforesaid problems with the histology‐based diagnosis, the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) established in 2012 new criteria stating that the biopsy could be avoided in symptomatic children with tTG‐ab value more than 10 times the upper limit of normal (ULN), positive EMA, and coeliac‐type genotype . There is increasing evidence to support the accuracy of these guidelines for paediatric coeliac disease if applied meticulously …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, biopsy is required for final evaluation in these cases. This invasive procedure, despite having been long considered the gold standard for diagnosis, is not pathognomonic and involves some misdiagnosis due to possible patchiness and observer dependency [7,10,11].…”
Section: Introductionmentioning
confidence: 99%